CLINICAL-DIAGNOSTIC AND PATHOGENETIC CHARACTERISTICS OF CEREBRAL DISORDERS IN PREMATURE NEWBORNS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The article presents the results of an analysis of the clinical and diagnostic features and pathogenetic mechanisms of cerebral disorders in premature newborns. The leading risk factors, morphofunctional changes in the central nervous system (CNS), early diagnostic methods, and modern therapeutic approaches are discussed. It has been shown that a combination of hypoxic-ischemic, infectious-inflammatory, and metabolic factors plays a key role in the formation of neurological dysfunctions. Particular attention is paid to the importance of neurosonography and magnetic resonance imaging (MRI) in the early diagnosis of brain lesions.